영아의 간혈관내피종에 대한 비수술적 치료경험 - 남소현(So-Hyun Nam); 박정익(Jeong-Ik Park); 김대연(Dae-Yeon Kim); 김성철(Seong-Chul Kim); 김인구(In-Koo Kim) (Annals of surgical treatment and research, 2010)
Purpose: Hepatic hemangioendothelioma (HET) is a rare benign vascular tumor in infants. The clinical manifestations are variable from asymptomatic to life-threatening heart failure or Kasabach-Merritt syndrome (KM SD). We report our non-surgical treatment experience for infantile HET. Methods: We analyzed 15 infants (5 males, 10 females) of HET retrospectively, from January 1989 to December 2007. Results: All except 2 were full-term babies and median birth weight was 3,140 g. The median age at diagnosis was 15 days of life (0∼157 days). Three of 5 patients diagnosed prenatally presented heart failure symptoms and the remaining 2 showed KM SD. Among 6 neonates, 3 showed cyanosis due to congestive heart failure. Nine patients showed multiple nodules at both liver lobes. Three asymptomatic patients were followed with radiologic examinations, thus HETs regressed spontaneously in two and decreased in one. Four cases that showed hepatomegaly or increase in size of subcutaneous hemangioma, were treated with prednisolone. All patients improved from tumor related symptoms and tumor size decreased. Four patients (2 patients of heart failure, 1 with rapid progressive hepatomegaly and 1 with congenital heart disease) received interferon-α. Among them, 3 showed regression of tumor and the remaining 1 showed decrease of tumor size. Two patients who suffered from severe heart failure received prednisolone and interferon-α, and then recovered. In the 2 patients with KM SD, we tried hepatic artery embolization with medical treatment. One survived but the other is not followed after failure of embolization. Conclusion: We experienced that many patients who had clinical symptoms associated with HET very early in their life treated with an aggressive nonsurgical treatment in symptomatic patients showed favorable outcome. KCI Citation Count: 0